Intensitas bermain game online dan kaitannya dengan kesehatan mental Generasi Z - Agustin, Annisa Intan; Kholifah, Nanik (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2025)
In recent years, there has been a significant increase in interest in mental health, especially among Generation Z, who have grown up in the digital age. Many members of Generation Z spend time playing online games. However, online game addiction can worsen their mental health. The purpose of this study was to investigate the impact of online game intensity on the mental health of Generation Z. A sample of 628 Generation Z students and 234 students of SMKN Tutur participated in this study using a quantitative approach with cluster random sampling. Data were collected using the Online Game Intensity Scale and the Mental Health Rating Scale, and the data were analyzed using simple linear regression analysis. The results showed a significant relationship between online game intensity and mental health problems. Thus, the hypothesis that online game intensity affects the mental health of Generation Z was accepted.